Effect of addition of Humic acid and seaweed extract and foliar application in some characteristics on fruit growth of olive ( Olea europaea L.) c.v Bashiqa - AL-Tememe, Zeinab Mohammedalywe; AL-Tamimi, Harith M. Aziz; AL-Asedy, Alaa A. Ali; AL-Amirry, Alaa Taleb (Journal of Kerbala for Agricultural Sciences, 2018)
The experiment was conducted in accordance with randomized complete design C. R. D in the private orchard in Fadhiliya village / Bashiqa district, Naynwa governorate during the growing season of 2012, to study the effect of treatment of olive trees Olea europaea L. by different concentrations of Humus and extract seaweed, which included experience using Humus addition three levels 0, 4 and 8 ml.L-1 and seaweed extract(Seaforcel) three levels 0, 4 and 8 ml.L-1 sprayed trees until all the moisture from seaweed extract three times during the growing season, first in 18/ 3 and 18/4 in the second and third in the 18/5/2012. All measurements were taken at mid-October 2012. Results showed superiority concentration 8m.L-1 Humus addition treatment gave increscent in fruit weight, length, flesh weight and N concentration. The effect of the interaction has exceeded the treatment of interaction between 8 ml. L-1Humus and 8 ml. L-1 seaweed extract in both the fruit weight and % of total nitrogen, while the treatment of the mixture was 4 ml. L-1Humus and 8 ml. L-1. A seaweed extract in the fruit-length ratio, while the interaction treatment exceeded 8 ml. L-1. Humus and 0 ml. L-1 seaweed extract in the average of flesh weight of fruits and excelled the treatment of interaction 8 ml. L-1 Humus and 4 ml. L-1 extract of seaweed in both of % oil in fruits and % of total protein.